2007
DOI: 10.1029/2006ja012120
|View full text |Cite
|
Sign up to set email alerts
|

Auroral NO+ 4.3 μm emission observed from the Midcourse Space Experiment: Multiplatform observations of 9 February 1997

Abstract: [1] The Spatial Infrared Imaging Telescope III (SPIRIT III) radiometer on the Midcourse Space Experiment satellite (MSX), observed enhanced 4.3 mm emission from a very well characterized aurora over the Barents Sea on 9 February 1997, in conjunction with observations by the POLAR and FAST satellites, the Loparskaya ground site, and ultraviolet and visible spectrometers aboard MSX. Measurements of the auroral location, form, spatial extent and dosing conditions were applied to specify the component of auroral 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The MSX program objectives, sensors and experiments are described by Mill et al [1994] and O'Neil et al [1994]. The characterization of high latitude infrared emissions from aurora [ Sharma et al , 2001; O'Neil et al , 2007] and PMCs was part of the MSX Earth limb background measurements program. Polar mesospheric cloud observations by the MSX ultraviolet and visible (UVISI) sensors are described by Carbary et al [1999, 2001, 2002, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…The MSX program objectives, sensors and experiments are described by Mill et al [1994] and O'Neil et al [1994]. The characterization of high latitude infrared emissions from aurora [ Sharma et al , 2001; O'Neil et al , 2007] and PMCs was part of the MSX Earth limb background measurements program. Polar mesospheric cloud observations by the MSX ultraviolet and visible (UVISI) sensors are described by Carbary et al [1999, 2001, 2002, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the 4.26 μm emission itself is susceptible to enhancements due to energetic particle precipitation during geomagnetic disturbances. This emission enhancement is known for both NO + (Mertens, Fernandez, et al., 2008; Mertens, Winick, et al., 2008; O’Neil et al., 2007) and CO 2 (Kalogerakis et al., 2016; Kumer, 1977; Sharma et al., 2015; Winick et al., 1987). The CO 2 auroral excitation results in NLTE, and has previously been discussed with regards to the Cross‐track Infrared Sounder (CrIS) NLTE observations in comparison to modeled NLTE radiances, which do not capture the full contribution to NLTE due to aurora (Z. Li et al., 2020), as models have assumed NLTE conditions that occur during the daytime.…”
Section: Introductionmentioning
confidence: 89%
“…The cooling process occurs due to the conversion of kinetic energy into radiative energy, which is then released into space and the lower atmosphere [14,15]. Based on satellite observations and auroral infrared detection experiments [25][26][27][28], it has been found that during the auroral disturbance, 5.3 µm radiation mainly derives from the ∆v = 1 band of NO, as shown in reaction (4):…”
Section: Introductionmentioning
confidence: 99%